Technical Workshop on Agricultural Insurance in Sri Lanka – Building a Knowledge Network and Partnerships - International Water Management Institute (2018)
The frequency and severity of extreme climate events are increasing the world over (IPCC 2014). The devastating effects of such events are intensified in areas where there are high rates of poverty and limited resources and capacity for disaster recovery. Risk sharing and transfer instruments like insurance are contributing to the efforts of governments and households to reduce immediate and long-term financial impacts associated with extreme weather events. These could go beyond supplying post-disaster liquidity for relief and reconstruction measures to also support ex-ante measures that reduce vulnerability. Resilient climate risk management that involves a balanced mix of approaches could also introduce insurance solutions as part of an ‘integrated climate risk management’ approach. The international community recognizes risk management and insurance as a means to managing climate-related risks during major global climate negotiations. Several initiatives have been taken by organizations to develop a comprehensive risk management framework that includes risk transfer tools such as insurance to address the loss and damage caused by extreme climatic events. Institutions are now placing considerable importance on agricultural risk management (ARM). The experience and knowledge gathered over the years could be used to develop more comprehensive strategies to cope with the risks faced by the agriculture sector. But insufficient knowledge transfer between countries, lack of a structured collection of lessons learned from management systems, as well as low uptake of innovations in ARM constrain development of such strategies. Organizations involved in these initiatives in Sri Lanka include national (the Ministry of Finance, National Insurance Trust Fund [NITF], Disaster Management Centre [DMC], Institute of Policy Studies of Sri Lanka [[IPS] and SANASA Federation Ltd.) and international (International Water Management Institute [IWMI], World Bank/Global Facility for Disaster Reduction and Recovery [GFDRR], and the International Labour Organization [ILO] of the United Nations [UN]. Within this context, IWMI, in collaboration with Epic Lanka, Fairfirst Insurance and other partners, identified the need to foster an exchange of knowledge and bring together the experiences on ARM available in Sri Lanka. The partnership aims to develop a more structured collection of data on good practices and lessons learned in ARM for the use of local policymakers and rural development practitioners. It also identifies the necessity of exploiting synergies among relevant development organizations to promote private sector partnerships that would generate greater impact for the insurance research community in Sri Lanka. A workshop on Agricultural Insurance held on Friday March 9, 2018 at the International Water Management Institute (IWMI) headquarters in Pelawatte, Battaramulla, took the initial steps towards achieving these aims. About 45 professionals from the public, private and development sectors involved in areas of insurance and research attended the sessions.